PENDIDIKAN AKHLAK DALAM SURAH AL-HUJURAT - Achyar Zein; Zulheddi Zulheddi; Efri Partahanan Harahap (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2022)
The background of this research is that there are still many Islamic educations in Indonesia that have not actualized the moral education contained in the source of Islamic teachings, namely the Koran. So this study aims to analyze the moral education contained in Surah Al-Hujurat/49 and connect it with moral education with Islamic educational institutions. The results of this study are expected to add new perspectives in order to apply them to the world of Islamic education contained in the Koran. The results of this study indicate that: 1) There is moral education in Surah Al-Hujurat, namely: First, moral education to Allah includes loving Allah more than loving anyone else by using Allah's word in the Qur'an as a guide and guidance in life, carrying out all his commands. and always leave His prohibitions and ask forgiveness from Allah swt. Second, moral education to the Apostle, namely giving birth to an attitude of gentle speech when together with the Apostle, and imitating his attitudes in doing in everyday life. Third, the moral education of fellow human beings, namely, all fellow human beings must always be kind in responding to information, resolve disputes between Muslims, and are not allowed to call with bad names and find fault with others.